TCO/Dielectric superlattice structures for the decoupling of electrical and optical properties - Caffrey, David (Trinity College (Dublin, Ireland). School of Physics, 2017)
In this thesis [Transparent Conducting Oxide (TGO)/Dielectric] superlattices are discussed as a methodology for the decoupling of optical and electrical properties and for the theoretical combining of the properties of disparate materials. This work will discuss why changing the refractive index of a material is a desirable achievement and how superlattice based effective TCOs can be employed to achieve this. The different analytical techniques used to assess the superlattices will then be outlined.
Keywords: Physics, Ph.D.; PhD Trinity College Dublin, 2017